Technological Pedagogical Content Knowledge (TPCK) on Mathematics Learning: A Literature Study - Safitri, Meilani; Aziz, M. Ridwan (Universitas Muhammadiyah Surakarta, 2022)
Technological Pedagogical Content Knowledge (TPCK) is currently gaining popularity as both a learning innovation and a research topic. This study is a literature review using a systematic literature review (SLR) method. The goal of this research is to describe various theories about TPCK, analyze various research results about TPCK, and describe various possibilities for the development and application of TPCK in mathematics learning. This study's data was gathered through a variety of books, articles, and research documents. Data analysis was carried out by synthesizing the results of the data source review. The findings of this study indicate that TPCK is highly likely to support mathematics learning, that TPCK can be developed and implemented in mathematics learning, and that TPCK development can take the form of models, teaching materials, and evaluation in mathematics learning.